(untitled) (Environment & Health, 2016)
Objective. We assessed a phytotoxic effect of various concentrations of diesel fuel (DF) on wheat and radish germination in the laboratory experiment for its further hygienic regulation in soil. Material and methods. We used a phytotesting method. Plants sensitive to the action of oil products (wheat and radish) were used as a test claimant under conditions of the simulation of maximum effect of diesel fuel. In the laboratory experiment we used DF according to DSTC 4840:2007 «Diesel Fuel. Improved Quality» manufactured by Аvias ITF LTD. Statistical processing of the material was performed applying the program package Microsoft Excel 2010 and STATISTICA v.6.1®. Results. During the laboratory experiment the concentrations of DF were established to inhibit the germination of seed and to retard the development of roots of the test plants not less than by 20% relatively to control. Conclusions. According to the results of the laboratory experiment a scientifically substantiated threshold concentration of diesel fuel, causing a phytotoxic effect, makes up 1500 mg/kg.